Factors Related To The Incidence of Anemia in Adolescent Girls at Mitra Inalum Private High School - Dea Sunjaya; Nofi Susanti (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Anemia in adolescent girls is a significant health issue. This condition can be influenced by various factors such as nutritional status, sleep quality, menstrual cycle, and duration of menstruation. This study aims to analyze the relationship between nutritional status, sleep quality, menstrual cycle, and duration of menstruation with the incidence of anemia among adolescent girls at Mitra Inalum Private High School. The study uses a quantitative method with a cross sectional approach. Data analysis was conducted univariately and bivariately using the Chi-Square test with the help of SPSS software. The research population consists of 125 adolescent girls at Mitra Inalum Private High School in 2025. The research sample consists of 95 adolescent girls selected using random sampling techniques based on inclusion and exclusion criteria. The results of the chi-square test indicate no significant relationship between nutritional status and the incidence of anemia (-value = 1.00). There is a significant relationship between quality. The quality of sleep is associated with the occurrence of anemia (p = 0.000). There is a significant relationship between the menstrual cycle and the occurrence of anemia (p = 0.001). There is a significant relationship between the duration of menstruation and the occurrence of anemia (p = 0.000). This study concludes that quality of sleep, menstrual cycle, and duration of menstruation have a significant relationship with the occurrence of anemia in female adolescents at SMA Swasta Mitra Inalum. Meanwhile, nutritional status does not show a significant relationship.